2021
DOI: 10.1111/phpp.12669
|View full text |Cite
|
Sign up to set email alerts
|

Citrulluside H and citrulluside T from young watermelon fruit attenuate ultraviolet B radiation‐induced matrix metalloproteinase expression through the scavenging of generated reactive oxygen species in human dermal fibroblasts

Abstract: Exposure to sunlight is essential for vitamin D biosynthesis; however, excessive exposure causes skin damage, mostly due to the ultraviolet radiation (UV-R) component of sunlight. Although UV-B only constitutes 5% of the ultraviolet rays reaching the earth, it causes considerably greater skin damage than UV-A (approximately 1000 times). Most UV-B radiation is absorbed in the epidermal layer;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In fact, we are not the first to isolate citrulluside T. Itoh et al [27] first isolated citrulluside H and citrulluside T from young watermelon fruits and reported that these two compounds attenuated ultraviolet B radiation-induced matrix metalloproteinase expression by scavenging reactive oxygen species produced by human skin fibroblasts. However, no studies have reported that compounds in the citrulluside family effectively inhibit melanogenesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, we are not the first to isolate citrulluside T. Itoh et al [27] first isolated citrulluside H and citrulluside T from young watermelon fruits and reported that these two compounds attenuated ultraviolet B radiation-induced matrix metalloproteinase expression by scavenging reactive oxygen species produced by human skin fibroblasts. However, no studies have reported that compounds in the citrulluside family effectively inhibit melanogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…The eluate obtained was subjected to compound isolation using 100% methanol on a column packed with Sephadex LH-20 to increase the purity (Figure 1). The isolated compounds were identified via NMR analysis, referring to the literature [26,27].…”
Section: Extraction and Isolation From The Citrullus Lanatus Stemmentioning
confidence: 99%
“…1821 We previously isolated phytol from watermelon sprouts and the novel phenolic glycosides citrulluside H (CH) and citrulluside T (CT) from young watermelon fruits, which showed anti-tumor and anti-oxidative activities, respectively. 2224…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] We previously isolated phytol from watermelon sprouts and the novel phenolic glycosides citrulluside H (CH) and citrulluside T (CT) from young watermelon fruits, which showed anti-tumor and anti-oxidative activities, respectively. [22][23][24] In this study, we further investigated the function of these recently isolated phenolic glycosides, including their inhibitory effects on the growth of C. acnes and inflammatory effects. C. acnes releases pro-inflammatory cytokines and chemokines via the innate immune receptors TLR2 and TLR4, and the 2 novel phenol glycosides induced anti-inflammatory effects by reducing the activity of nuclear factor κB (NF-κB), which is activated by TLRs.…”
Section: Introductionmentioning
confidence: 99%